2022
DOI: 10.1007/s12088-022-01029-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Journey: Mount Everest to Mars

Abstract: A rigorous exploration of microbial diversity has revealed its presence on Earth, deep oceans, and vast space. The presence of microbial life in diverse environmental conditions, ranging from moderate to extreme temperature, pH, salinity, oxygen, radiations, and altitudes, has provided the necessary impetus to search for them by extending the limits of their habitats. Microbiology started as a distinct science in the mid-nineteenth century and has provided inputs for the betterment of mankind during the last 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 116 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…Extensive research has significantly advanced the understanding of bacteria, particularly concerning their lifecycle. From the earliest investigations into basic phenomena, such as food fermentation, research has progressed to uncovering the presence of disease-causing pathogens in diverse ecological niches, including plant rhizosphere soil, deep ocean zones, alpine peaks, and other extreme environments [1]. Among the notable discoveries is the phenomenon of cell-to-cell communication, known as "quorum sensing," which occurs within bacterial communities, both within and between species.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has significantly advanced the understanding of bacteria, particularly concerning their lifecycle. From the earliest investigations into basic phenomena, such as food fermentation, research has progressed to uncovering the presence of disease-causing pathogens in diverse ecological niches, including plant rhizosphere soil, deep ocean zones, alpine peaks, and other extreme environments [1]. Among the notable discoveries is the phenomenon of cell-to-cell communication, known as "quorum sensing," which occurs within bacterial communities, both within and between species.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ]. Generally, such extreme habitats are considered to be uninhabitable by most lifeforms [ 3 ]. However, some studies have reported that the polar regions’ (comprising the Antarctic, Arctic, and Tibetan Plateau) soils harbor distinct survival patterns of microbial diversity and exhibit dominant, special functional phylotypes that adapt to harsh conditions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yang et al investigated the Planococcus halotolerant Y50 T that was isolated from the Tibet Plateau, which possessed the ability of petroleum degradation, as well as antioxidant, radiation resistance, and cold adaptation [ 5 ]; further, Lentzea tibetensis FXJ1.1311 T was isolated from the soil of the Tibetan Plateau, which showed antimicrobial activity against Gram-positive bacteria and Fusarium oxysporum [ 6 ]. Additionally, more novel microbial resources with special functions formed by adaptation to such extreme environments could survive here [ 3 , 7 , 8 , 9 ]. As we all know, the high-altitude Mount Everest in the Tibetan Plateau region of China has currently been receiving a large amount of solar radiation—and the higher the altitude, the more cosmic rays it receives [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation